Religion on the battlefield - Hassner, Ron E. (Cornell University Press, 2016)
"How does religion shape the modern battlefield? Ron E. Hassner proposes that religion acts as a force multiplier, both enabling and constraining military operations. This is true not only for religiously radicalized fighters but also for professional soldiers. In the last century, religion has influenced modern militaries in the timing of attacks, the selection of targets for assault, the zeal with which units execute their mission, and the ability of individual soldiers to face the challenge of war. Religious ideas have not provided the reasons why conventional militaries fight, but religious practices have influenced their ability to do so effectively. In Religion on the Battlefield, Hassner focuses on the everyday practice of religion in a military context: the prayers, rituals, fasts, and feasts of the religious practitioners who make up the bulk of the adversaries in, bystanders to, and observers of armed conflicts. To show that religious practices have influenced battlefield decision making, Hassner draws most of his examples from major wars involving Western militaries. They include British soldiers in the trenches of World War I, U.S. pilots in World War II, and U.S. Marines in Iraq and Afghanistan. Hassner shows that even modern, rational, and bureaucratized military organizations have taken--and must take--religious practice into account in the conduct of war"--